Different reading styles for Mathematics text - Berger, M (Springer, 2019)
A broad categorisation of different reading styles for mathematics text is generated in this research. The styles derive from those found in literature around academic reading skills. These styles are inductively refined using video transcripts of five specially chosen students studying out loud from a prescribed mathematics textbook. The context is a self-study mathematics course directed at high school mathematics teachers with weak content knowledge. Reading is understood as a transaction (enacted curriculum) between text (written curriculum) and reader. Reading styles are characterised in terms of depth of reading, focus on different components of text or not, connections within text or to prior knowledge, and performance on exercises. Five different styles of reading mathematics text are identified: close reading with strong connections, close reading with some connections, scanning, skimming, and avoiding. The different reading styles are also interpreted in terms of structure, voice, and genre of the textbook. © 2019, Springer Nature B.V.
Keywords: Enacted curriculum; Form of address; Learner’s use of mathematical textbook; Mathematics reading styles; Mathematics textbook analysis; Written curriculum